‘Playing in the Dark’ with Portuguese Statues in the United States of America: João Rodrigues Cabrilho, Peter Francisco, and Catarina de Bragança - Silva, Reinaldo Francisco (2012)
Representations of the Portuguese in American literature are clearly predicated on prevailing theories of race in America. As Eric Sundquist has claimed in To Wake the Nations, this former slaveholding country is one where “race remains very much at the center of [...] experience.” Race and racism, Toni Morrison reminds us in Playing in the Dark, are issues that literary critics have resisted addressing, as “silence and evasion have historically ruled literary discourse.” Like Morrison, I also wish to “identify those moments when American literature was complicit in the fabrication of racism.” “Racism,” Morrison argues, “is as healthy today as it was during the Enlightenment.” It is now widely accepted that Americans have been obsessed by skin color and that the darker complexion of Southern Europeans has produced anxiety and discomfort in Americans of Northern European stock. This rhetoric was also applied to the three historical figures represented by the statues evoking three major figures associated with American culture. To name, two that were actually erected on American soil (João Rodrigues Cabrilho in San Diego, California, and Peter Francisco in several Portuguese communities in the United States) and one that never made it to inauguration, Catarina de Bragança. The erection of these statues honoring Portuguese historical figures was mostly perceived as a means to counter patronizing attitudes towards Portuguese Americans or for motives associated with ethnic pride, racism, and recognition. If American literature was shaped by racial discourse, this paper will argue that it was also applied to art in general, that is, even statues such as these were “played” with because of the “darkness” evoked by these three historical figures.